Relationship value dimensions: identifying a viable model - Baxter, RA (Queensland University of Technology, 2006)
This paper describes alternative models of intangible value, in business to business buyer-seller relationships, to the one reported by Baxter and Matear (2004). The perspective is that of the seller. Using Baxter and Matear’s dimensions, it provides theoretical arguments, based on the resource based view, the intellectual capital literature, and other conceptual bases, for the model as compared with three rival models. The empirical evidence to date in support of the original model is discussed.